2019
DOI: 10.3390/su11205688
|View full text |Cite
|
Sign up to set email alerts
|

Green Infrastructure Solutions to Health Impacts of Climate Change: Perspectives of Affected Residents in Detroit, Michigan, USA

Abstract: Cities worldwide are incorporating green infrastructure to mitigate climate change and achieve health cobenefits. However, green infrastructure projects are often distributed inequitably based on race and class. Residents’ perspectives are necessary to develop and enact effective and equitable ‘green’ strategies to address climate change and its health impacts. This study reports findings from interviews and ethnographic observations with diverse residents of Detroit, Michigan, USA, who have experience with bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…A study that interviewed residents of Detroit, Michigan had expressed support for green infrastructure projects. However, many interviewees had felt an unclear responsibility towards maintaining the structures due to inadequate communication between the residents and the city government and a lack of proper governance [ 65 ]. Interview participants from another study from Atlanta, Georgia had revealed a similar lack of trust and negative perceptions from the community about the local government.…”
Section: Discussionmentioning
confidence: 99%
“…A study that interviewed residents of Detroit, Michigan had expressed support for green infrastructure projects. However, many interviewees had felt an unclear responsibility towards maintaining the structures due to inadequate communication between the residents and the city government and a lack of proper governance [ 65 ]. Interview participants from another study from Atlanta, Georgia had revealed a similar lack of trust and negative perceptions from the community about the local government.…”
Section: Discussionmentioning
confidence: 99%
“…U-M Grounds and Facilities, local municipalities, and the community at large will need to be consulted on all projects to identify areas where green infrastructure and stormwater management would be most beneficial. In Michigan cities, interviews with residents show widespread support for green infrastructure solutions, but residents were concerned about governance and maintenance (Carmichael, Danks, and Vatovec 2019). See Appendix I for costbenefit resources for green infrastructure in comparison to conventional methods.…”
Section: A Plant Trees To Increase Canopy Covermentioning
confidence: 99%
“…Particularly within the framework of urban greening or urban redevelopment (also called "urban revitalization" or "urban renewal"), GSI implementers must consider how GSI practices affect communities, especially residents that may have been excluded from the benefits of past investments in GSI or be skeptical of interventions that are not perceived as "of" or "for" their communities [110,243]. More research is needed to understand who stands to benefit from GSI, especially when it is embedded in larger developments [33,34]. Integrating a socioeconomic lens from the beginning of GSI project assessment can also help address the often-disconnected nature of overlapping and conflicting goals and strategies of various groups-too often prioritized on the basis of economics alone [37]-within a single planning effort.…”
Section: Prioritize Goalsmentioning
confidence: 99%
“…While sustainable development has incorporated both the language of GSI and social equity in its rise to prominence, the two have yet to be adequately considered in tandem [33,34]. Doing so requires an analysis of both the procedural (who participates in decision making) and distributional (who benefits, and how) aspects of environmental justice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation